Pengaruh Terpaan Media Akun Media Sosial Instagram @Infocegatansukoharjo terhadap Penyampaian Informasi Bagi Followers - Hidayah Putra Wijaya; Budi Santoso (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study analyzes the influence of media exposure from the Instagram account @infocegatansukoharjo on the dissemination of information to its followers. This study was motivated by the growing role of Instagram as a local digital communication medium capable of delivering information quickly, conveniently, and in a way that meets the needs of the Sukoharjo community. This study employs a quantitative approach using an online survey of 114 respondents who are followers of the @infocegatansukoharjo account. Media exposure was measured using the indicators of frequency, duration, and attention, while information delivery was measured using information satisfaction, self-identity, integration, and entertainment. The data were analyzed using descriptive statistics and simple linear regression. The results show that media exposure has a positive and significant effect on information delivery, with a significance value of 0.000, a t-value of 11.489, and a coefficient of determination of 54.1%. These findings indicate that the @infocegatansukoharjo account plays a crucial role in strengthening the dissemination of local information via Instagram.